Effects of Frozen Red Dragon Fruit Consumption on Metabolic Markers in Healthy Subjects and Individuals at Risk of Type 2 Diabetes - Flores-Verastegui, Mildred Inna Marcela; Coe, Shelly; Tammam, Jonathan; Almahjoubi, Haythim; Bridle, Robyn; Bi, Sabina; Thondre, Pariyarath Sangeetha (Nutrients, 2025)
Background/Objectives: The interest in creating new products to decrease the risk of developing non-communicable chronic diseases such as type 2 diabetes (T2D) is increasing. These products include traditional food sources used as part of diverse cultures around the world, such as dragon fruit. The aim of this study was to investigate the effects of a frozen red dragon fruit (FRDF) beverage on blood pressure, glycaemic response (GR) and insulinaemic response (IR), lipid profile (LP), total antioxidant status (TAS), and C-reactive protein (CRP) levels in healthy subjects and individuals at risk of T2D. Methods: A parallel design trial (UREC registration number 211527; ClinicalTrials.gov registration number NCT05199636/19 January 2022) lasting four weeks and involving three testing sessions was conducted; participants were randomly assigned to one of two treatments (following general health guidance or consuming FRDF beverage). Systolic and diastolic blood pressures were taken; venous blood samples were collected to determine the LP and CRP levels; and capillary blood samples were taken before and after consuming a standard glucose drink to evaluate GR and IR at 15 min intervals (first hour) and 30 min intervals (second hour). Results: Eighteen participants completed this study, nine healthy (28.44 ± 5.20 years) and nine at risk (31.78 ± 12.11 years). The daily consumption of an FRDF-based beverage for four weeks by individuals at risk of T2D resulted in a reduction in blood pressure and IR–incremental area under the curve. The LP showed a downward trend, and a significant difference between treatments (p = 0.009) was found for CRP levels. Conclusions: Beverages based on FRDF may have the potential to decrease the risk of T2D.